Frictions in the interbank market and uncertain liquidity needs: Implications for monetary policy implementation - Monika Bucher; Achim Hauck; Ulrike Neyer (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2014)
This paper shows that depending on the distribution of banks' uncertain liquidity needs and on how monetary policy is implemented, frictions in the interbank market may reinforce the effectiveness of monetary policy. These frictions imply that with its lending and deposit facilities the central bank has an additional effective instrument at hand to impose an impact on bank loan supply. While lowering the rate on the lending facility has, taken for itself, an expansionary effect, lowering the rate on the deposit facility has a contractionary effect. This result has interesting implications for monetary policy implementation at the zero lower bound.
Keywords: E52; E58; G21; 330; interbank market; monetary policy; monetary policy implementation; zero lower bound; loan supply